DESIGN AND CONSTRUCTION OF ANIMAL FEED PACKAGING MACHINE USING A MANUAL MEASURING AND PRESS SYSTEM WITH VARIABLE SPEED - Rizki Ardika Akbar; Bobby Alvian Juliansah; Elisa Sulistyorini (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2026)
A packaging machine is a tool that functions to carry out the work of packaging production products in an industrial process. The main purpose of designing this packaging machine is to make the animal feed packaging process faster, more accurate, and more efficient in terms of energy use. The working principle of this packaging machine uses a measuring system that moves back and forth continuously, where the measuring adjusts the volume of the type of animal feed that is packaged, so that the packaging process becomes shorter and more accurate. Therefore, the concept of speed control of an induction motor using Variable Frequency Drive (VFD) can be applied as a control system to adjust the speed of the electric motor according to the needs of the workload. The research method used is experimental research, which is to make a tool and conduct a direct function test to determine the level of measurement accuracy. The test results show that the machine is able to carry out the process of measuring and packaging animal feed more effectively and efficiently. In addition, the use of VFD allows the adjustment of working speed according to production needs, while the press system uses a hand impulse sealer to produce neater packaging and has a better selling value. The machine designed is expected to be a solution for livestock business actors and MSMEs in increasing productivity and quality of animal feed packaging. Keywords: packaging machine, measuring system, hand impulse sealer, induction motor, Variable Frequency Drive (VFD)